Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Find the explicit forumula for the solution of Cauchy problem on ${\mathbb{R}^ + } \times \mathbb{R}$

$\left\{ \begin{gathered} {u_t} - k{u_{xx}} + b{u_x} + cu = 0 \\ u\left( {0,x} \right) = g\left( x \right) \\ \end{gathered} \right.$

I started by substituting $v\left( {t,x} \right) = u\left( {t,x} \right){e^{ct}}$ which gives $\left\{ \begin{gathered} {v_t} - k{v_{xx}} + b{v_x} = \left( {{u_t} + cu - k{u_{xx}} + b{u_x}} \right){e^{ct}} = 0 \\ v\left( {0,x} \right) = g\left( x \right) \\ \end{gathered} \right.$

however, I don't know what to do next to get rid of the $b{v_x}$ term.

EDIT: $k,b,c$ are constants

share|cite|improve this question
Try $v(t,x)=u(t,x)e^{\alpha t+\beta x}$ and see if you can choose $\alpha,\beta$ to kill off more terms. – user53153 Jan 19 '13 at 15:31
Yes, that murders all pesky terms – Alen Jan 19 '13 at 15:59
up vote 2 down vote accepted

By using the substitution $v\left( {t,x} \right) = u\left( {t,x} \right){e^{\left( {c + \frac{{{b^2}}} {{4k}}} \right)t - \frac{b} {{2k}}x}}$ , the problem becomes $\left\{ \begin{gathered} {v_t} - k{v_{xx}} = 0 \\ v\left( {0,x} \right) = g\left( x \right){e^{ - \frac{b} {{2k}}x}}\\ \end{gathered} \right.$

which has the solution $v\left( {t,x} \right) = \frac{1} {{\sqrt {4\pi kt} }}\int_{ - \infty }^{ + \infty } {{e^{ - \frac{{{{\left( {x - y} \right)}^2}}} {{4kt}}}}g\left( y \right){e^{ - \frac{b} {{2k}}y}}} dy$, giving $u\left( {t,x} \right) = {e^{ - \left( {c + \frac{{{b^2}}} {{4k}}} \right)t + \frac{b} {{2k}}x}}\frac{1} {{\sqrt {4\pi kt} }}\int_{ - \infty }^{ + \infty } {{e^{ - \frac{{{{\left( {x - y} \right)}^2}}} {{4kt}}}}g\left( y \right){e^{ - \frac{b} {{2k}}y}}} dy$

share|cite|improve this answer

Case $1$: $k=0$ and $b=0$

Then $u_t+cu=0$




$\ln u(t,x)=-ct+f(x)$


$u(0,x)=g(x)$ :


$\therefore u(t,x)=g(x)e^{-ct}$

Case $2$: $k=0$ and $b\neq0$

Then $u_t+bu_x+cu=0$


Follow the method in

$\dfrac{dt}{ds}=1$ , letting $t(0)=0$ , we have $t=s$

$\dfrac{dx}{ds}=b$ , letting $x(0)=x_0$ , we have $x=bs+x_0=bt+x_0$

$\dfrac{du}{ds}=-cu$ , letting $u(0)=f(x_0)$ , we have $u(t,x)=f(x_0)e^{-cs}=f(x-bt)e^{-ct}$

$u(0,x)=g(x)$ :


$\therefore u(t,x)=g(x-bt)e^{-ct}$

Case $3$: $k\neq0$

Then $u_t-ku_{xx}+bu_x+cu=0$

Let $u(t,x)=T(t)X(x)$ ,

Then $T'(t)X(x)-kT(t)X''(x)+bT(t)X'(x)+cT(t)X(x)=0$




$\begin{cases}T(t)=c_3(s)e^{-\frac{t(4k^2s^2+b^2+4kc)}{4k}}\\X(x)=\begin{cases}c_1(s)e^{\frac{bx}{2k}}\sin xs+c_2(s)e^{\frac{bx}{2k}}\cos xs&\text{when}~s\neq0\\c_1xe^{\frac{bx}{2k}}+c_2e^{\frac{bx}{2k}}&\text{when}~s=0\end{cases}\end{cases}$

$\therefore u(t,x)=\int_0^\infty C_1(s)e^{\frac{2bx-t(4k^2s^2+b^2+4kc)}{4k}}\sin xs~ds+\int_0^\infty C_2(s)e^{\frac{2bx-t(4k^2s^2+b^2+4kc)}{4k}}\cos xs~ds$

$u(0,x)=g(x)$ :

$\int_0^\infty C_1(s)e^{\frac{bx}{2k}}\sin xs~ds+\int_0^\infty C_2(s)e^{\frac{bx}{2k}}\cos xs~ds=g(x)$

$e^{\frac{bx}{2k}}\int_0^\infty C_1(s)\sin xs~ds=g(x)-e^{\frac{bx}{2k}}\int_0^\infty C_2(s)\cos xs~ds$ or $e^{\frac{bx}{2k}}\int_0^\infty C_2(s)\cos xs~ds=g(x)-e^{\frac{bx}{2k}}\int_0^\infty C_1(s)\sin xs~ds$

$\mathcal{F}_{s,s\to x}\{C_1(s)\}=g(x)e^{-\frac{bx}{2k}}-\mathcal{F}_{c,s\to x}\{C_2(s)\}$ or $\mathcal{F}_{c,s\to x}\{C_2(s)\}=g(x)e^{-\frac{bx}{2k}}-\mathcal{F}_{s,s\to x}\{C_1(s)\}$

$C_1(s)=\mathcal{F}^{-1}_{s,x\to s}\left\{g(x)e^{-\frac{bx}{2k}}\right\}-\mathcal{F}^{-1}_{s,x\to s}\{\mathcal{F}_{c,s\to x}\{C_2(s)\}\}$ or $C_2(s)=\mathcal{F}^{-1}_{c,x\to s}\left\{g(x)e^{-\frac{bx}{2k}}\right\}-\mathcal{F}^{-1}_{c,x\to s}\{\mathcal{F}_{s,s\to x}\{C_1(s)\}\}$

$\therefore u(t,x)=\int_0^\infty \mathcal{F}^{-1}_{s,x\to s}\left\{g(x)e^{-\frac{bx}{2k}}\right\}e^{\frac{2bx-t(4k^2s^2+b^2+4kc)}{4k}}\sin xs~ds-\int_0^\infty\mathcal{F}^{-1}_{s,x\to s}\{\mathcal{F}_{c,s\to x}\{C_2(s)\}\}e^{\frac{2bx-t(4k^2s^2+b^2+4kc)}{4k}}\sin xs~ds+\int_0^\infty C_2(s)e^{\frac{2bx-t(4k^2s^2+b^2+4kc)}{4k}}\cos xs~ds~\text{or}~\int_0^\infty C_1(s)e^{\frac{2bx-t(4k^2s^2+b^2+4kc)}{4k}}\sin xs~ds+\int_0^\infty\mathcal{F}^{-1}_{c,x\to s}\left\{g(x)e^{-\frac{bx}{2k}}\right\}e^{\frac{2bx-t(4k^2s^2+b^2+4kc)}{4k}}\cos xs~ds-\int_0^\infty\mathcal{F}^{-1}_{c,x\to s}\{\mathcal{F}_{s,s\to x}\{C_1(s)\}\}e^{\frac{2bx-t(4k^2s^2+b^2+4kc)}{4k}}\cos xs~ds$

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.